2021
DOI: 10.3390/ijerph18115705
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization in Different Stages among Patients with Dementia: A Nationwide Population-Based Study

Abstract: To evaluate the trend of healthcare utilization among patients with dementia (PwD) in different post-diagnosis periods, Taiwan’s nationwide population database was used in this study. PwD were identified on the basis of dementia diagnoses during 2002–2011. We further subdivided the cases into 10 groups from the index year to the 10th year after diagnosis. The frequency of emergency department visits and hospitalizations, the length of stay, outpatient and department visits, and the number of medications used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…The odds of long-term stay among people with dementia were considerably higher than people with other chronic conditions (Willink et al, 2016). The increase in nursing home use is associated with cognitive impairment and dementia progression due to challenges for families and caregivers, such as patients' escalating dependence on others, limitations of activities of daily living, and behavioral and psychiatric symptoms (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The odds of long-term stay among people with dementia were considerably higher than people with other chronic conditions (Willink et al, 2016). The increase in nursing home use is associated with cognitive impairment and dementia progression due to challenges for families and caregivers, such as patients' escalating dependence on others, limitations of activities of daily living, and behavioral and psychiatric symptoms (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…People with ADRD prefer to age in place and receive the care and treatments they need at home or in the location of their choice with comfort as long as possible (Wagner, 2021). However, evidence indicates that the emergency department admission and hospitalization rate increases as individuals' cognitive impairment progresses (Chen et al, 2021). Sociodemographic characteristics (e.g., education, race, and ethnicity) and health factors (e.g., cognitive impairment, limitations in activities of daily living, and the number of chronic conditions, collectively known as frailty) are associated with disparities in ACP and healthcare utilization and the type of healthcare settings used, such as home or hospital (Mah et al, 2021;Pereira et al, 2022;Rahemi, 2019;Rahemi et al, 2019;Rahemi & Williams, 2016Suntai et al, 2022).…”
Section: Applications Of Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of dementia is vast as it acts on individuals living with dementia (people living with dementia), their families and informal caregivers, the health care system, and society 1 . Healthcare service utilization and consequently health care costs represent a tremendous social and economic burden 4–6 . For example, a meta‐analysis from Germany found that, although healthcare costs for people living with dementia living at home are lower compared to the costs of people living with dementia who are institutionalized, higher total societal costs can be found among people living with dementia at home due to the higher informal care time 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Healthcare service utilization and consequently health care costs represent a tremendous social and economic burden. [4][5][6] For example, a meta-analysis from Germany found that, although healthcare costs for people living with dementia living at home are lower compared to the costs of people living with dementia who are institutionalized, higher total societal costs can be found among people living with dementia at home due to the higher informal care time. 4 To address the dementia challenge, the World Health Organization (WHO) strongly recommends strengthening national dementia healthcare delivery.…”
mentioning
confidence: 99%